Antigenic characterization of the oligosaccharide portion of the lipooligosaccharide of nontypable Haemophilus influenzae. - Patrick, C C (1987)
Monoclonal antibodies (MAbs) directed against epitopes in the oligosaccharide portion of the lipooligosaccharide (LOS) of nontypable Haemophilus influenzae (NTHI) were used to characterize the LOS of this pathogen. Western blot (immunoblot) analysis with four LOS-specific MAbs and proteinase K-derived LOS preparations from 69 NTHI strains allowed the classification of these strains into nine LOS antigenic groups. The use of these MAbs in a more sensitive colony blot radioimmunoassay system together with these same NTHI strains identified 14 LOS antigenic groups. Extensive cross-reactivity was detected between the LOS epitopes of these NTHI strains and the LOS of H. influenzae type b. The epitopes recognized by these MAbs were not accessible to antibody on the surface of every strain. These LOS epitopes were also not stably expressed by NTHI growing in vitro; the observed frequency of LOS antigen variation ranged from 1 to 24% when large numbers of colonies of NTHI strains were screened for reactivity with the LOS-directed MAbs in the colony blot radioimmunoassay. This LOS antigenic variation was sometimes associated with alterations in the profile of the LOS molecule as resolved by dodecyl sulfate-polyacrylamide gradient gel electrophoresis followed by staining with silver. These data indicate that considerable antigenic diversity exists among NTHI strains with regard to the oligosaccharide epitopes in their LOS molecules.